Influences of strain rate on mechanical behaviors of unsaturated and quasi-saturated loess under varying drainage conditions - Tongwei Zhang; Sheng Li; Hengxing Lan; Huyuan Zhang; Fanyu Zhang (Journal of Rock Mechanics and Geotechnical Engineering, 2025)
Although time-dependent deformation of geomaterials underpins slope-failure prediction models, the influence of strain rate on shearing strength and deformation behavior of loess remains unclear. The consolidated undrained (CU) and drained (CD) triaxial testing elucidated the impact of strain rate (0.005–0.3 mm/min) on strength envelopes, deformation moduli, pore pressures, and dilatancy characteristics of unsaturated and quasi-saturated loess. Under drained conditions with a controlled matric suction of 50 kPa, increasing strain rates from 0.005 mm/min to 0.011 mm/min induced decreases in failure deviatoric stress (qf), initial deformation modulus (Ei), and cohesion (c), while friction angles remained unaffected. Specimens displayed initial contractive volumetric strains transitioning to dilation across varying confining pressures. Higher rates diminished contractive volumetric strains and drainage volumes, indicating reduced densification and strength in the shear zone. Under undrained conditions, both unsaturated and quasi-saturated (pore pressure coefficient B = 0.75) loess exhibited deteriorating mechanical properties with increasing rates from 0.03 mm/min to 0.3 mm/min. For unsaturated loess, reduced contractive volumetric strains at higher rates manifested relatively looser structures in the pre-peak stress phase. The strength decrement in quasi-saturated loess arose from elevated excess porewater pressures diminishing effective stresses. Negative porewater pressures emerged in quasi-saturated loess at lower confining pressures and strain rates. Compared to previous studies, the qf and Ei exhibited rate sensitivity below threshold values before attaining minima with marginal subsequent influence. The underlying mechanism mirrors the transition from creep to accelerated deformation phase of landslides.